Pengelolaan Alokasi Dana Desa Berbasis Maqashid Syariah di Padakkalawa, Kabupaten Pinrang - Ismail Hasang; Nasir Hamzah; Ambo Asse; Mukhtar Lutfi; Muhammad Nasri Katman (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
The aim of this research is to determine the management of Village Fund Allocation (ADD) based on Maqashid Syariah in Padakkalawa Village, Pinrang Regency. The type of research used in this research is qualitative descriptive research with a phenomenological approach. Respondents interviewed in this research were Village Heads, Village Officials, BPD Chairmen, Village Financial Management Implementers (PPKD), Hamlet Heads, Religious Leaders, Community Leaders, Youth Leaders in Padakkalawa Village. The analysis techniques used are data reduction, data display and drawing conclusions/verification. The results obtained in this research are that the Padakkalawa Village Government manages the Village Fund Allocation (ADD) by adhering firmly to the principles of maqashid sharia, this can be seen from the implementation of maintaining religion through the application of religious values, honest and thorough recording, reporting accurately. true and accurate; maintaining the soul through working with attention to the safety of the soul (BPJS Employment); maintaining reason through working with a healthy mind/mind and not speculating; maintaining offspring through community (youth) involvement; as well as maintaining assets through effective and efficient use of the budget, increasing Village Original Income (PADes).